Gestión de la educación y desempeño del docente universitario de una facultad de ingeniería - Perú (LACCEI, 2024)
The management of university education has gained relevance and investigative interest with the advent of the pandemic, since the educational and administrative virtuality has allowed improvements in management processes. In this way, the purpose of the study was to establish the influence of educational management on the performance of the university professor of a Faculty of Engineering in Lima. It has been based on a quantitative approach and descriptive and explanatory scope, with the voluntary participation of 216 university students from a faculty of engineering studies in Lima. The results showed an efficient level in the management of education (76.9%) and a good level in the performance of the university teacher (67.6%) according to the perception of the university students. Therefore, it was concluded that the management of education does influence the performance of the university teacher, being significant (p = 0.000 0.05) and a 76.5% variability in which the model is valid to predict the performance of the teacher.